Digital Governance of Project Management System using Soft Systems Methodology , Case Study of SOE Holding Survey Services (IDSurvey) - Budi Prakoso; Rachma Fitriati (International Journal of Science and Society, 2023)
This article aims to establish the digital governance of the project management system at PT Biro Klasifikasi Indonesia (BKI). As a holding company for BUMN Survey Services (IDSurvey), although there is already a Decree of the BKI Board of Directors No. DU.007/HK.303/KI-21 concerning Refinement of Business Portfolio Determination for SBU (Strategic Business Unit) Function Improvement, but in practice, there are still various obstacles in BKI project management, such as delays in project completion and target mismatches in project management. This study uses a qualitative method with a soft systems methodology approach with research time from January to August 2023 at the BKI Head Office. By using e-government, digital governance, and project management, the study results show that BKI needs to develop a standard operating procedure for digital governance of project management in order to succeed in the project. This study recommends that after the SOP for Digital Governance of the Management System is made, the SVP of Commercial Business Operations, as the leading sector, needs to socialize and disseminate the governance SOP that is made.